2021
DOI: 10.1186/s12912-021-00687-z
|View full text |Cite
|
Sign up to set email alerts
|

Burdens, resources, health and wellbeing of nurses working in general and specialised palliative care in Germany – results of a nationwide cross-sectional survey study

Abstract: Background Palliative care in Germany is divided into general (GPC) and specialised palliative care (SPC). Although palliative care will become more important in the care sector in future, there is a large knowledge gab, especially with regard to GPC. The aim of this study was to identify and compare the burdens, resources, health and wellbeing of nurses working in GPC and SPC. Such information will be helpful for developing prevention programs in order to reduce burdens and to strengthen resou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 55 publications
1
15
0
2
Order By: Relevance
“…Intuitively, intention to leave profession (within past year) is, with 25 of 100 possible points, valued relatively low within our sample. However, it outranges the corresponding mean score of the reference group as well as a large German sample from diverse occupational settings [ 24 ], and is at the upper edge of the spectrum in the German nursing sector [ 40 – 42 ]. Results of the NEXT study showed that, amongst others, higher quantitative demands and more work-privacy conflicts (as observed within our sample) increase intention to leave the profession in nurses [ 29 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intuitively, intention to leave profession (within past year) is, with 25 of 100 possible points, valued relatively low within our sample. However, it outranges the corresponding mean score of the reference group as well as a large German sample from diverse occupational settings [ 24 ], and is at the upper edge of the spectrum in the German nursing sector [ 40 – 42 ]. Results of the NEXT study showed that, amongst others, higher quantitative demands and more work-privacy conflicts (as observed within our sample) increase intention to leave the profession in nurses [ 29 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent scoping review identified enhanced team relationships and finding meaning in work as important resources to handle ethical challenges during a pandemic [ 48 ]. Both might be sources of resilience, helping nurses deal with the multitude of hardships experienced during the Covid-19 pandemic [ 6 , 40 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The specialized literature on job satisfaction reveals that it is an integral part of any industry or work environment. In the case of health workers, it was found that ethical leadership positively and significantly influences job satisfaction, by: applying ethical principles to problem-solving and equity [ 24 ]; offering training and organizational support [ 25 ] together with management support and resources, despite tendencies to quit the job [ 26 ]; offering psychological support despite difficult working conditions [ 27 ]; prompting risk prevention plans [ 28 ]; offering improved health maintenance programs [ 29 ]. In all the previously mentioned sources, well-being was either positively or negatively affected by management decisions.…”
Section: Introductionmentioning
confidence: 99%
“…Interactions created through online channels cannot form effective relational relationships because of the lack of interpersonal connections (Driver, 2018). Loneliness is an effective predictor of mental health and well-being (Diehl et al, 2021;Dinu et al, 2022;Kaufmann and Vallade, 2020;McIntyre-Mills et al, 2018;Wright, 2014), student engagement (Stoliker and Lafreniere, 2015), academic performance (Fan et al, 2021;Singh et al, 2021;Yalçın et al, 2020), lack of sense of community (Reedy, 2019), and dropout intentions (Alkan, 2014). Thus, it is necessary to explore the possible effect of loneliness on student learning experiences (Kaufmann and Vallade, 2020), such as student engagement and academic achievement.…”
mentioning
confidence: 99%